La moda étnica: su problemática en torno a la apropiación cultural en el Perú - Amoretti Lamadrid, Elsa Maria (Pontificia Universidad Católica del Perú, 2023)
Ethnic fashion can be problematic due to the very fine line that exists between the inspiration that can be used in the creation of designs and cultural appropriation. There are innumerable cases in which big brands, usually international, use typical designs of a culture belonging to a minority without any type of authorization from these people.This non-consensual use comes to generate harm to the member of these communities, both economically and socially, which is why some countries, in order to reduce these damages, have regulated this issue. Thus, this research seeks to develop key subjects such as ethnic fashion and cultural appropriation, as well as to analyze the current Peruvian situation regarding cultural appropriation.

La moda étnica puede llegar a ser problemática debido a la muy delgada línea que existe entre la inspiración que se puede tener en la creación de diseños y la apropiación cultural. Existen innumerables casos en los que marcas grandes, usualmente internacionales, utilizan diseños propios de alguna cultura perteneciente a un pueblo minoritario sin ninguna clase de autorización por parte de estos pueblos. Este uso no consentido llega a generar un perjuicio a los miembros de estas comunidades, tanto económico como social, es por ello que algunos países, a fin de reducir estos perjuicios, han normado este tema. Es así que esta investigación busca desarrollar temas clave como lo son la moda étnica y la apropiación cultural, así como analizar la situación peruana actual frente a la apropiación cultural.
Ethnic fashion: its problem around cultural appropriation in Peru
Keywords: Ethnic fashion; Cultural appropriation; Regulation; Peru; Protection; Moda étnica; Apropiación cultural; Regulación; Perú; Protección; https://purl.org/pe-repo/ocde/ford#5.05.00